Reaksi Pasar Terhadap Pengumuman Right Issue (Studi Peristiwa pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Revanda Galih Bella Novita; Alien Akmalia (Universitas Muhammadiyah Jember, 2022)
This study aims to examine the market reaction to the right issue announcement of companies listed on the Indonesia Stock Exchange during 2019-2021. This study using the event study method with a research sample from 34 companies. Using window period for 11 days, which are 5 days before right issue announcement, 1 day at right issue announcement, and 5 days after right issue announcement. The secondary data used in this study were obtained from the Indonesia Stock Exchange, Fact Books, and Yahoo Finance, and selected by using purposive sampling method. The results of this study indicate that there is a market reaction to the announcement of the rights issue which is indicated by the abnormal return around the announcement date; there is no difference of abnormal returns before and after the right issue announcement; and there is no difference in trading volume activity before and after the right issue announcement. The findings of this study can help investors make decisions when dealing with rights issue shares. Investors should seek information about the actions of rights issue events issued by issuers, as well as the intended use of the proceeds from the rights issue activities. Companies should also explain why they are conducting a rights issue so that investors have fully transparent information.